Diary of an awesome friendly kid : Rowley Jefferson's journal - Kinney, Jeff. (London : Penguin Random House : Puffin, 2019)
"In his first journal, middle schooler Rowley Jefferson, Greg Heffley's sidekick, records his experiences and misguided decision to write a biography of Greg, who, in his own mind, is destined to become rich and famous"--OCLC.
5-8.
5-8
1020L
Keywords: Heffley, Greg -- Juvenile fiction; Heffley, Greg -- Fiction; Heffley, Greg -- Fiction; Best friends -- Juvenile fiction; Boys -- Juvenile fiction; Diaries -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous stories; Schools -- Juvenile fiction; Best friends -- Fiction; Boys -- Fiction; Diaries -- Fiction; Friendship -- Fiction; Humorous stories; Schools -- Fiction; Boys -- Fiction; Diaries -- Fiction; Friendship -- Fiction; School stories; Diary fiction; Humorous fiction